Working conditions and quality work in the field of civil construction of Metropolitan Lima - Falcón R., Giovana G. (2016)
This research deals with evaluating the persistence of inadequate working conditions to improve labor quality and productivity in the civil construction sector in Metropolitan Lima is one of the most serious national problems affecting the working class at the high rate accidents and construction companies that have additional costs in fines and civil damages to those affected. This research is a concern of engineers and technicians who developed a first approach to the problem of the persistence of inadequate working conditions affecting labor quality and productivity in the civil construction sector in Metropolitan Lima. Provides, from a conceptual and legal perspective, the various technical aspects indicating mechanisms for their protection. Finally a number of general conclusions about the current situation and the vision of experts, along with recommendations to minimize the persistence of inadequate working conditions are presented.